Efeito do treinamento resistido e suplementação do picolinato de cromo sobre a composição corporal e função contrátil de cardiomiócitos de ratos obesos - Estevãm, Wagner Müller (2018)
Introduction: Obesity is a complex multifactorial disease characterized by excessive accumulation of adipose tissue, described as an independent risk factor for cardiovascular diseases. The elevation of adipose tissue promotes consequences to heart characterized by changes in ventricular remodeling, systolic and diastolic dysfunction. Supplementation with chromium picolinate (PiCr) has been used to promote decreased body fat and increased muscle mass. While physical training is used as a non-pharmacological tool in reducing body weight and minimizing risks related to obesity. Resistance training (RT) is reported for benefits in improving body composition and cardiac function. However, the association between PiCr supplementation and RT on body adiposity and cardiac function in the obesity condition needs to be investigated. Objective: To evaluate the body composition and myocardial performance of obese rats supplemented with PiCr and submitted to RT. Methods: Wistar rats were induced and exposed to the condition of obesity and redistributed in the following groups: Control (C); Control supplemented with PiCr (CSp); Control submitted to RT (CRT); Control supplemented with PiCr submitted to RT (CSpRT) ;; Obese (Ob); Obese supplemented with PiCr (ObSp); Obese submitted to RT (ObRT) and Obese supplemented with PiCr submitted to RT (ObSpRT). C groups received standard diet and the Ob groups high-fat diet. The RT protocol consisted of climbing a vertical ladder performed for 8 weeks, for 3 times a week. RT consisted of 4 to 5 series with progressive intensities of 50%, 75%, 90% and 100% of the maximum load. After that, if the animal completed the 4th series it was submitted to 5th series with 100% of the maximum load plus30g. Nutritional analysis, blood pressure, glycemic, lipidic and hormonal profiles, determination of water content on lung and liver was performed. In addition, the total weight of the heart and its relation to tibia length were analyzed. Cardiomyocytes the contractile function was performed. Data were expressed as mean ± standard deviation or median ± interquartile range. The comparisons between groups C and Ob were performed by student’s t test. Two-way ANOVA was used to compare the other groups, complemented by Bonferroni or Holm-Sidak post hoc tests. The level of significance was 5%. Results: It was observed that the final body weight and body fat in the Ob group were statistically different in relation to C. However, supplementation with PiCr and RT did not promote change in these variables. The results of the present study show that the obesity condition promoted a punctual impairment of the contractile function of cardiomyocytes evidenced by the reduction of the percentage of shortening, however, the lower T50% Relax, suggesting a protective effect of obesity on myocardial relaxation. Considering the treatments isolated with PiCr or RT in the obesity condition, preserved contractile function of cardiomyocytes was visualized. In contrast, the interaction between PiCr and RT promotes myocardial relaxation damage. Conclusion: RT associated with PiCr supplementation at obesity condition was not able to modify the body composition and attenuate the cardiac damage, evidenced by the reduction of the percentage of shortening. In addition, the interaction between treatments, resistance training and supplementation with chromium picolinate, leads to myocardial relaxation dysfunction.